PENGARUH WORK-FAMILY CONFLICT DAN WORKLOAD TERHADAP KINERJA PERAWAT DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING - Khoiriyah, Saadatul; Adiwati, Mei Retno; Ayundha Evanthi (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the influence of work-family conflict and workload on nurse performance with job stress as a mediating variable among nurses at RSUD Ibnu Sina Gresik. Nurses who are married and have children often face dual role conflicts and excessive workloads, both of which can reduce their job performance and service quality. This research uses a quantitative approach with Structural Equation Modeling based on Partial Least Square (SEM-PLS). A total of 122 nurses were selected using purposive sampling technique. The variables measured include work-family conflict, workload, job stress, and nurse performance, with data collected through a structured questionnaire. The findings show that both work-family conflict and workload have a negative and significant impact on nurse performance, either directly or indirectly through job stress. Job stress is proven to mediate the relationship between the two independent variables and performance. These results highlight the need for hospital management to implement adaptive work policies, align workload with nurse capacity, and provide professional and emotional support through training and counseling to maintain optimal healthcare service quality.